2005
DOI: 10.1086/426920
|View full text |Cite
|
Sign up to set email alerts
|

The Third VLBA Calibrator Survey: VCS3

Abstract: We present the third extension to the Very Long Baseline Array (VLBI ) Calibrator Survey, containing 360 new sources not previously observed with very long baseline interferometry (VLBI). The survey, based on three 24 hour VLBA observing sessions, fills the areas on the sky above declination À45 where the calibrator density is less than one source within a 4 radius disk at any given direction. The positions were derived from astrometric analysis of the group delays determined at 2.3 and 8.6 GHz frequency bands… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(175 citation statements)
references
References 23 publications
5
168
0
Order By: Relevance
“…4) -systematically lower than the one measured in the parsec-scale cores of typical bright extragalactic Doppler-boosted core-jet sources (e.g., Kovalev et al 2005;Pushkarev & Kovalev 2011, in prep.). The .…”
Section: Properties Of the Dominating Parsec-scale Componentsmentioning
confidence: 73%
See 1 more Smart Citation
“…4) -systematically lower than the one measured in the parsec-scale cores of typical bright extragalactic Doppler-boosted core-jet sources (e.g., Kovalev et al 2005;Pushkarev & Kovalev 2011, in prep.). The .…”
Section: Properties Of the Dominating Parsec-scale Componentsmentioning
confidence: 73%
“…(11) Comments: COINS -the source is part of the COINS (Peck & Taylor 2000); COINS-REJ -the source was considered as a candidate for the COINS sample but was rejected (Peck & Taylor 2000); GPS -GPS source, part of the RATAN-600 GPS sample Sokolovsky et al (2009) unless indicated otherwise, for these sources approximate spectral peak frequency (in GHz) is indicated; GPS-REJ the source was reported in the literature as a GPS candidate, but was not confirmed by RATAN-600 observations; STEEP -steep spectrum source, FLAT -flat spectrum source. (12) To distinguish between resolved and unresolved components we use the criterium proposed by Kovalev et al 2005: ψ > HPBW 4 ln 2 π ln SNR SNR−1 where ψ is the component best-fit angular size, HPBW is the Half Power Beam Width, SNR is the signal to noise ratio of the component. (13) No RATAN-600 observations available for this source.…”
Section: Discussionmentioning
confidence: 99%
“…These sources are mainly drawn from the Radio Fundamental Catalogue (RFC) comprising all sources observed with VLBI for astrometry and geodesy programmes. They also include data from major VLBI surveys such as the VLBA Calibrator Survey (e.g., Beasley et al 2002;Petrov et al 2005;Kovalev et al 2007), the VLBI Imaging and Polarimetry Survey (Helmboldt et al 2007;Petrov & Taylor 2011), and the VLBA 2-cm Survey Kellermann et al (1998Kellermann et al ( , 2004, among others. For their sample of sources, they fit two circular Gaussian components to the self-calibrated visibilities for each source, then select the most compact component as the core component for which they determine the FWHM angular sizes.…”
Section: Published Vlbi Core Sizesmentioning
confidence: 99%
“…The ICRF2 consists of a catalog with the VLBI coordinates of 3414 extragalactic radio sources (from which 295 are defining sources). It was constructed from all geodetic and astrometric VLBI data acquired so far, including those from the Very Long Baseline Array (VLBA) Calibrator Survey (VCS; Beasley et al 2002;Fomalont et al 2003;Petrov et al 2005Petrov et al , 2006Kovalev et al 2007;Petrov et al 2008). It has a noise floor in position of about 60 μas and an axis stability of 10 μas.…”
Section: Introductionmentioning
confidence: 99%